POWER LOSSES SENSITIVITY TO ELECTRICAL POWER SYSTEMS TRANSITS CHANGES - Lezhnyuk, Petro; Burykin, Olexandr; Lesko, Vladyslav (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents the method of an estimation of electrical power system (EPS) mode parameters sensitivity to changes in the nodes load. Possibility of sensitivity to changes in the nodes load of other systems estimation allows to estimate sensitivity of losses in transit overflows in separate EPS elements. The method is based on using the calculation and estimation algorithms as well as calculative programs of electric networks with transformer communications interference.